ABOUT THE INTRODUCTION OF VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN SCHOOLS - Sarsimbayeva С.М.; Mukasheva М.У.; Kornilov Ю.В.; Omirzakova А.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article considers the factors contributing to the introduction of virtual and augmented reality technologies in the schools. Among the factors mentioned are: the emergence of large companies, the growth of investment in the industry. These factors contributed the emergence of large number of virtual and augmented reality software, lower prices for infrastructure. Another factor was the understanding of the market, how to use VR/AR technologies in education, the psychological readiness of the education sector to implement these technologies. The article also notes the unsolved problems in the implementation of these technologies, such as the lack of methods for implementing these technologies in the school educational process, the lack of a methodology for justifying the use of VR/AR technologies as a modern means of teaching and learning in secondary schools. The obtained research results help to contribute to solving problems of digitalization in the field of education.